MicroRNA-28-5p as a potential diagnostic biomarker for chronic periodontitis and its role in cell proliferation and inflammatory response - Pengcheng Huang; Linghui Jia (Elsevier, 2022)
Background/purpose: Recent studies have pointed to the crucial role of microRNAs (miRNAs) in chronic periodontitis (CP). This study investigated the regulation and potential mechanisms of miR-28-5p in CP patients and lipopolysaccharide (LPS)-induced periodontal ligament cells (PDLCs). Materials and methods: 76 CP patients and 71 periodontally healthy subjects were included. RT-qPCR was employed to examine miR-28-5p and sphingosine kinase −1 (SPHK1) in subjects' gingival sulcus fluid and PDLCs. The diagnostic performance was evaluated by measuring the area under the curve (AUC) of the receiver operating characteristic (ROC) analysis. Pearson correlation coefficient (r) was adopted to explore the statistical relation between indicators. PDLCs proliferation and inflammation factors were determined by CCK-8 and ELISA assay. The direct target gene was validated by a dual-luciferase reporter assay. Results: miR-28-5p was lowly expressed in CP patients and LPS-induced PDLCs (P < 0.05). AUC for miR-28-5p was 0.937, which had certain diagnostic value. Additionally, miR-28-5p was negatively correlated with periodontal clinical indicators and inflammatory factors. Cell proliferation of PDLCs was inhibited and inflammation was promoted under LPS induction, however, elevated miR-28-5p diminished the effect of LPS (P < 0.05). SPHK1 acts as a miR-28-5p target and the elevation of SPHK1 caused by LPS treatment was inhibited by the increased miR-28-5p. Conclusion: Present study revealed that miR-28-5p could be served as a potential diagnostic biomarker for CP. And miR-28-5p may participate in CP progression by targeting SPHK1 to regulate the proliferation and inflammation of PDLCs. This study may offer insights into CP treatment and diagnosis.